Patterns of Care for Atrial Fibrillation Before, During, and at Discharge From Hospitalization: From the Get With The Guidelines–Atrial Fibrillation Registry. (April 2021) - Desai, Nihar R.; Sciria, Christopher T.; Zhao, Xin; Piccini, Jonathan P.; Turakhia, Mintu P.; Matsouaka, Roland; Fonarow, Gregg C.; Lewis, William R.
Abstract : Background: Atrial fibrillation (AF) is the most common arrhythmia encountered in the hospital. However, contemporary treatment of patients hospitalized with AF, including stroke prevention, switching between these therapies, and rhythm control interventions are not well studied. We aimed to examine trends in inpatient interventions for AF, including switching oral anticoagulation (warfarin to direct oral anticoagulants [DOACs]), cardioversion, catheter ablation, and amiodarone use in hospitalized patients with AF. Methods: Using data from the Get With The Guidelines—AFIB registry from the American Heart Association, we analyzed patterns of medication and procedure use among hospitalized patients with AF from January 3, 2013, to March 28, 2017. To identify significant predictors of switching, multivariable hierarchical regression models were developed with patient baseline characteristics and comorbidities. Results: Among 31 280 patients with AF from 97 participating hospitals, 47.1% were on anticoagulation at presentation (6695 warfarin and 7393 DOAC) and the majority were continued at discharge (91.1%). Of those who were not receiving anticoagulation before hospitalization, 60.6% started anticoagulation at discharge (25.0% warfarin and 75.0% DOAC). The prevalence of switching from warfarin to DOAC was 4.0% and was more likely with younger age and lower CHA2 DS2 -VASc. Among 28 143 patients (excluding those discharged from the emergency department or observation status), 32.0% underwent cardioversion (56.1% chemically assisted and 49.4% electrical), 6.4% AF ablation, and 1.0% left atrial appendage occlusion device implantation. Patients of White race, younger age, and lower CHA2 DS2 -VASc were significantly more likely to undergo cardioversion or AF ablation, while older patients with higher CHA2 DS2 -VASc were significantly more likely to be initiated on amiodarone. Conclusions: Despite guideline recommendations prioritizing DOAC therapy, there are relatively low rates of switching from warfarin to DOAC in patients hospitalized with AF. Moreover, there is substantial variation in switching and utilization of rhythm control strategies, highlighting opportunities for performance improvement. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.